Development and characterization of a novel bio-based brake fluid using roselle oil with copper oxide Nano additive - Aliyu, Abdulkabir; Kaisan, Muhammad Usman; Dandajeh, Hamisu Adamu; Ramalan, Usman Ibrahim (Human Resource Management Academic Research Society, 2024)
Conventional brake fluids, which are typically derived from petroleum-based sources, pose environmental hazards due to their non-biodegradable nature. A bio-based brake fluid was produced from roselle oil with Nano copper oxide as an additive. The tribological, and Physicochemical properties of the blended brake fluid were evaluated. From the kinematic viscosity analysis, it was observed that there was a linear increase in the viscosity with an increase in the nanoparticle with a 43.3% increase in viscosity due to the inclusion of 0.3 wt.% of CuO nanoparticle. The increment is attributed to physical barriers created by the nanoparticle that generate more internal friction to the flow of oil molecules. The addition of 0.1 wt.% and 0.2 wt.% of CuO nanoparticles increases the viscosity index from 373.9 to 381.3, and 374.6 respectively. The flash point of the blended roselle oil was observed to be 199 ℃. The inclusion of 0.1 wt.%, 0.2 wt.% and 0.3 wt.% CuO nanoparticles at 0.1% rate, increase the flash point to 202 ℃, 209 ℃, and 210 ℃ respectively. This indicates that adding the nanoparticles improves the surface area-to-volume ratio, enabling the fluid to absorb heat more efficiently. The coefficient of friction (CoF) of the pure roselle oil was 0.117 while the CuO nanoparticle included roselle oil was observed to be 0.067, 0.104, and 0.057 at CuO nanoparticle quantity of 0.1 wt.%, 0.2 wt. and 0.3 wt.% respectively. The wear rate of aluminum with the oil as a brake fluid was 0.3729 mm3n -1m-1 , 0.4316 mm3n -1m-1 , and 0.3592 mm3n -1m-1 at a nanoparticle reinforcement of 0.1 wt.%, 0.2 wt.%, and 0.3 wt.% respectively. The reduction in the CoF and wear rate indicated that the CuO nanoparticles acted as solid lubricants themselves, forming a protective layer between the sliding surfaces. The production of bio-based brake fluid offers novelty in this research area and this achievement represents a significant step towards developing eco-friendly and sustainable alternatives to conventional petroleum-based brake fluids.